Input Efficiency as a Solution to Externalities and Resource Scarcity: A Randomized Controlled Trial - Alpizar, Francisco; Carpio, Maria Bernedo Del; Ferraro, Paul J. (The University of Chicago Press, 2023)
Resource-conserving technologies are widely reported to benefit both the people who adopt them and the environment. Evidence for these “win-win” claims comes largely from modeling or nonexperimental designs, and mostly from the energy sector. In a randomized trial of water-efficient technologies, the ex-ante engineering estimate of water use reductions was three times higher than the experimental estimate, a divergence arising from engineering and behavioral reasons other than the rebound effect. Using detailed cost information and experimentally elicited time and risk preferences, we infer that the private welfare gains from adoption are, on average, negative, implying no “efficiency paradox”.